Multidisciplinary challenges in mastocytosis and how to address with personalized medicine approaches - Valent, Peter; Akin, Cem; Gleixner, Karoline V.; Sperr, Wolfgang Reinhard; Reiter, Andreas; Arock, Michel; Triggiani, Massimo (International journal of molecular sciences, 2019)
Mastocytosis is a hematopoietic neoplasm defined by abnormal expansion and focal accumulation of clonal tissue mast cells in various organ-systems. The disease exhibits a complex pathology and an equally complex clinical behavior. The classification of the World Health Organization (WHO) divides mastocytosis into cutaneous forms, systemic variants, and localized mast cell tumors. In >80% of patients with systemic mastocytosis (SM), a somatic point mutation in KIT at codon 816 is found. Whereas patients with indolent forms of the disease have a normal or near-normal life expectancy, patients with advanced mast cell neoplasms, including aggressive SM and mast cell leukemia, have a poor prognosis with short survival times. In a majority of these patients, multiple somatic mutations and/or an associated hematologic neoplasm, such as a myeloid leukemia, may be detected. Independent of the category of mastocytosis and the serum tryptase level, patients may suffer from mediator-related symptoms and/or osteopathy. Depending on the presence of co-morbidities, the symptomatology in such patients may be mild, severe or even life-threatening. Most relevant co-morbidities in such patients are IgE-dependent allergies, psychiatric, psychological or mental problems, and vitamin D deficiency. The diagnosis and management of mastocytosis is an emerging challenge in clinical practice and requires vast knowledge, a multidisciplinary approach, and personalized medicine procedures. In this article, the current knowledge about mastocytosis is reviewed with special emphasis on the multidisciplinary aspects of the disease and related challenges in daily practice.
Gesehen am 11.09.2019